Shaping a holistic national innovation system. Riigi tervikliku innovatsioonisüsteemi kujundamine - Reiljan, Janno; Paltser, Ingra (Estonian Discussions on Economic Policy, 2016)
For the sustainable economic development of a state the functioning national innovation system (NIS) is needed. NIS covers different government policies (for instance, education policy, R&D policy innovation support to business sector, intellectual property protection, public procurement policy, etc.). All these policies have to be integrated in a holistic system through innovation policy enabling the functioning different policies in mutual relationships smoothly and effectively for sustainable economic development. The goal of this article is to highlight the role of innovation policy in shaping a holistic NIS. The first part of the article deals with the need for public sector intervention in innovation processes and problems resulting from it. In the second part a holistic NIS model that reflects the role of innovation policy is developed and presented. The third part deals with the structure of innovation policy based on a holistic NIS model